Strategy Marketing In Increase Amount Customer Financing Bank Sharia In Indramayu - Sharifah (Penerbit Hellow Pustaka, 2023)
This article aims to explore how marketing strategies are used to increase the number of financing customers at Bank Jabar Banten Syariah KCP Indramayu, and what are the obstacles faced by marketing lending in increasing the number of financing customers at Bank Jabar Banten Syariah KCP Indramayu. The research method used in this study is a type of field research using qualitative research methods. The research method used to examine the condition of natural objects that describe a data in the form of writing, pictures, and numbers that have been obtained in the form of a narrative. From the research results obtained, the marketing strategy used by Bank Jabar Banten Syariah KCP Indramayu is a strategy that is used in general such as the marketing mix which includes product, price, distribution, promotion by advertising, personal selling, sales promotion and also publicity. Apart from using this strategy, there are several more specific strategies, namely by conducting a Memorendum of Understanding (MoU), Top Up and outreach. And the obstacles faced by marketing lending are rate competition for third party funds with other banks, obstacles in the process of disbursing funds which can be considered quite long compared to other banks. And another obstacle is the lack of understanding from the public about Islamic Banks.